The Effect of Token Economy Implementation on Disruptive Behavior in Early Childhood - Okta Nihayah, Fifin; Nur Aisiyah, Laily; Haidlor, Muhammad (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2025)
Background of the study: Disruptive behavior refers to actions that tend to oppose or interfere with a child's interactions with peers and adults. This type of behavior has a negative impact because it can disrupt the learning process, and therefore, requires proper intervention. In general, such negative behaviors need to be modified in order to be reduced. The token economy technique is a form of behavior modification designed to increase targeted positive behaviors and decrease undesired behaviors through the use of tokens as reinforcement. Aims and scope of paper: This study aims to determine the effect of implementing a token economy on disruptive behavior in children. Methods: The research method used was a quasi-experimental design with a non-equivalent control group. This study was conducted at ARNI Kindergarten in Jember. The sampling technique used was convenience sampling, involving children from groups A2 and A3, totaling 28 children as research subjects. Data on children's disruptive behavior were collected through observation using an observation sheet instrument containing indicators of disruptive behavior. Data analysis was conducted using an Independent Sample T-test, with all analyses performed using the SPSS program. Results: The results of the Independent Sample T-test showed that the calculated t-value was greater than the critical t-value (t = 2.818 > 1.782) and in a negative direction (-), indicating a significant difference in children's disruptive behavior before and after the implementation of the token economy. This suggests that the token economy effectively reduces disruptive behavior in group A children at ARNI Kindergarten, Jember. Contribution: This study specifically examines the impact of using a token economy on children’s disruptive behavior. It provides valuable insights for teachers in addressing disruptive behavior through the application of token economy strategies. Reducing such behavior can help children learn more effectively and contribute to creating a comfortable and conducive learning environment.